Biochemical responses to bicarbonate supplementation on biomass and lipid productivity of Chlorella Sp. BTA9031 isolated from Coalmine area. Issue 5 (23rd March 2017) - Mondal, Madhumanti; Ghosh, Ashmita; Oinam, Gunapati; Tiwari, O.N.; Gayen, K.; Halder, G.N.
Abstract : The present study aims towards the investigation of lipid production capability of microalgae isolated from coal mining site. The biomass production and lipid productivity of the isolate was studied under the influence of different bicarbonate, nitrate, and phosphate concentration. The production of biomass was observed to be highest at 8.4, 0.75, and 0.06 gL −1 of bicarbonate, nitrate, and phosphate concentrations. The role of bicarbonate supplementation under different nutritional starvation conditions viz. N+ P+, N– P–, N+ P–, and N– P+ with and without sodium bicarbonate respectively was also evaluated. Addition of sodium bicarbonate increased the lipid content to 35% of dry cell weight (DCW) and carbohydrate content to 52% of DCW under the nitrate and phosphate nutritional starvation conditions. The results revealed that the microalgae grown in sodium bicarbonate can be a promising feedstock for biodiesel production. © 2017 American Institute of Chemical Engineers Environ Prog, 36: 1498–1506, 2017